The Urgency of Deaf Students and their Efforts to Improve Writing English Skills - Khoirul Huda; Oikurema Purwati; Pratiwi Retnaningdyah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The management of the Ngurah Rai Grand Forest Park shows a dualist side. The plan to hand over the management of the Ngurah Rai Grand Forest Park to the Regional Government of Bali has effected a grassroots conflict regarding the customary rights of the local community. This study aims to design a model of participation for coastal communities in the Ngurah Rai Grand Forest Park, Pemogan Village. This research uses the Ladder of Citizen Participation theory (Arnstein, 1969) as the main theory and the Evolutionary Model of Tourism Partnerships as the supporting theory (Jamal & Getz, 1995) and also the concepts of participation, partnership, CBT, social capital, and government regulation. Data collection techniques used observation, structured interviews, and FGD. This study used the technique of qualitative research data analysis (Sugiyono, 2011)This research shows that community participation has developed through some stages such as (a) non-participation; (b) tokenism; (c) citizen power. The form of community participation is Community Based Participation implemented by the Fishing Community Group of Simbar Segara and Mina Lestari Batu Lumbang. And the other hand Government-Based Participation is implemented by the Mangrove Information Center. The finding of this research is the Mix-Based Participation Model. The recommendation is that the government should take the role of mediator to solve various conflicts at the grassroots level due to the traditional claims of the management of Ngurah Rai Grand Forest Park by two customary villages i.e. Pemogan and Kepaon.